Results of Politics on Academia in Universities of Pakistan - Sultana, Naveed (International Journal of Psychosocial Rehabilitation, 2020)
Politics in education is controversial issue in Pakistan. In history under military rulers, political activities of teachers unions and student’s unions were kept banned but it couldn't be implemented in democratic era. Democracy without education is hypocrisy rather than an instrument for social change. Functions of education and democracy both are to motivate, improve and develop society. Teachers' role in politics may be investigated properly. This study was aimed to determine the teachers’ interest and involvement in politics, its effects at higher level of education in Pakistan and to find out solution of the problem. 200 teachers from 5 federal universities were taken as sample. The results emerged that majority of male teachers supported that politically well-aware students of can play positive role in the improvement of the society. Majority of female teachers pleaded for academic excellence. Study recommends realistic and beneficial political activities to be encouraged by teachers in universities.